Design and Implementation of Medical Ultrasound Remote Control Software Based on Sensor Design - Deng, Shuhao; Jiang, Quan; Zhang, Yingchun; Lu, Xin; Shi, Xiurong; Zhang, Yuan (Frontiers in Bioengineering and Biotechnology, 2021)
In recent years, with the continuous development of mobile communication technology, the Internet has gradually transitioned from the traditional mode to the mobile device access mode, which has brought great convenience to people's work and life. Based on this, this paper designs a medical ultrasound remote control software based on sensor design. The system software communicates with the stimulator through the Bluetooth port of the mobile phone, and can send the parameter information input by the mobile phone to the field programmable gate array of the stimulator for compilation and processing. The upper computer control interface with remote communication function is written by Lab VIEW software. Socket is used to establish the inter-network process connection, and the medical ultrasonic equipment simulates the hardware key input according to the received control instructions, so as to achieve the purpose of remote control. At the same time, the controls interacting with users are customized to improve the user experience.